KARAKTERISASI BAKTERI POTENSIAL PENDEGRADASI OLI BEKAS PADA TANAH BENGKEL DI KOTA PADANG - Ahda, Yuni; Fitri, Lel (IAIN Batusangkar, 2016)
The research objective is to locate and determine the morphological and biochemical characteristics of the bacteria that could potentially degrade the used lubricant oil in the workshops in Padang. The research was conducted March to October 2016. The bacteria obtained from the workshop is cultured on selective media MSM and transferred to LB medium to obtain pure isolates. Morphological and biochemical characterization indicate three types of bacteria that live in workshop?s soil contaminated used lubricant oil, namely Bacillus sp1, sp2 and Alcaligenes Bacillus sp